Artificial Phototropic Systems for Enhanced Light Harvesting Based on a Liquid Crystal Elastomer. (21st October 2021) - Yan, Yichen; Zhao, Yusen; Alsaid, Yousif; Yao, Bowen; Zhang, Yucheng; Wu, Shuwang; He, Ximin
Abstract : Artificial Phototropic Systems In article number 2000234, Ximin He and co‐workers present a versatile, low‐cost mechanically strong artificial phototropic system able to autonomously track sunlight. The double‐leg bimorph design allows the system to achieve large‐angle reorientation and device load‐bearing simultaneously. Using this sunlighttracking system, the oblique‐incidence‐induced energy‐density loss can be recovered for photovoltaics and solar vapor generation processes, enabling enhanced solar energy harvesting and device performance.